The effect of different 6-benzylaminopurine (BAP) concentrations on axillary branching of Clinacanthus nutans - Mohamad, Fatin Haziqah (2016)
Sabah Snake Grass with the scientific name, Clinacanthus nutans belongs to the Acanthaceae family. It has several important uses such as treatment for eye diseases, treat injuries from fall, remove blood clots, and others. This plant originates from Malaysia, Indonesia, Thailand, Vietnam, and China and can be propagated by using seed or stem-cutting. But, propagation by stem cutting produces limited plant production. Therefore, the objective of this study is to trigger axillary branching on C. nutans plants by using different concentrations of 6-Benzylaminopurine (BAP). The study was conducted using randomized complete block design (RCBD). The experimental materials for this study were the semi-hardwood stem cuttings with four nodes. The stem cuttings were planted in pots containing a mixture of sand and perlite at 1:1 ratio. They were allowed to root and grow to a height of 15-20 cm before the terminal buds were decapitated. The nodes of the plants were sprayed with different BAP concentrations (0, 25, 50, 75, 100 mg/L) and the plants were watered twice daily. Most BAP treatment triggered axillary branching except for 50 mg/L BAP. The highest number of buds proliferated was obtained at 100 mg/L BAP concentration, but the highest length of axillary branching was obtained at 0 mg/L BAP which is the control treatment.